EFEKTIVITAS PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) PASCA PANDEMI DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Cahyono; Dadang Mulyana; Lili Sukarliana; Syifa Nurul Latiefah (STKIP Subang, 2023)
This study aims to determine whether the effectiveness of limited face-to-face learning has an effect on improving student learning outcomes, during learning during the current pandemic and new normal. The method used in this study is a quantitative approach with survey methods and the independent variable analysis is the effectiveness of limited face-to-face learning (PTMT) and the dependent variable is Student Learning Outcomes. The research sample used by the researcher is simple random sampling. The samples used by the researchers were class VIII A, VIII B, and VIII C. Furthermore, data collection in this study used a questionnaire/questionnaire and interviews. Researchers process the results of the analysis data, including technical analysis of normality, homogeneity, simple linear regression, coefficient of determination, and the last is hypothesis testing. Research results the results of data analysis tests by researchers prove that students in the effectiveness of the implementation of limited face-to-face learning (PTMT) on student learning outcomes have good response results. Based on the results of the research hypothesis testing using the t-test showing the value of t count = 4.661 > 0.1735, it can be seen that the limited face-to-face learning effectiveness variable (PTMT) has an effect on learning outcomes. It can be concluded that the factors that influence the results of the study are 21% that students feel the effectiveness of implementing limited face-to-face learning (PTMT) is effective and optimal. It is proven that the implementation of limited face-to-face learning will have an effect on increasing student learning outcomes. It can be concluded that there are differences in learning outcomes when the implementation of online learning and PTMT takes place.